Epicardial adipose tissue thickness and growth differentiation factor 15 in axial spondyloarthritis - OKÇU, MEHMET (My University, 2022)
Objectives: To investigate growth differentiation factor-15 (GDF-15) levels and the thickness of epicardial adipose tissue (EAT) in patients with axial spondyloarthritis (axSpA) and to evaluate their relationship with functional status, disease activity, disease duration, and the type of medical treatment received by the patients.Methods: This cross-sectional study was carried out at Kirsehir Ahievran University School of Medicine between February and June 2020. Twenty-nine healthy controls and 44 patients with axSpA were included in the study. Gender, age, erythrocyte sedimentation rate, GDF-15, body mass index, complete blood count, ejection fraction, the EAT thickness, and C-reactive protein of all participants were recorded. Ankylosing Spondylitis Quality of Life Index, Bath Ankylosing Spondylitis Functional Index, the disease duration, Bath Ankylosing Spondylitis Metrology Index, and Bath Ankylosing Spondylitis Disease Activity Index scores of patients with axSpA were noted.Results: Epicardial adipose tissue thickness values (0.35 +/- 0.09 cm) in the AxSpA group were higher compared to the control group (0.26 +/- 0.06 cm) (p<0.01). Growth differentiation factor-15 levels of the control group and axSpA group were similar. The treatment received by the patients did not have a significant relationship with EAT thickness and GDF-15. Bath Ankylosing Spondylitis Functional Index scores, disease duration, and age were significantly positively correlated with GDF-15 levels.Conclusion: In this study, EAT thickness values were found to be significantly higher in the axSpA group. In addition, GDF-15 was positively correlated with age, Bath Ankylosing Spondylitis Functional Index score, and disease duration.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; axial spondylarthritis; growth differentiation factor 15; epicardial adipose tissue; ankylosing spondylitis; DISEASE-ACTIVITY INDEX; ANKYLOSING-SPONDYLITIS; RHEUMATOID-ARTHRITIS; TURKISH VERSION; CARDIOVASCULAR-DISEASE; BATH; RELIABILITY; VALIDATION; ASQOL; RISK